Management control and leadership styles in family business: An Indonesian case study. Issue 1 (2nd March 2015) - Efferin, Sujoko; Hartono, Monika S.
Abstract : Purpose: This study aims to provide insight into the meaning and perceptions of leadership and its subsequent management control system (MCS) practices in family business in less developed countries. More specifically, the study attempts to understand the cultural context of family business and its importance in developing its leadership and MCS, the production and reproduction processes of the culture into the MCS and the resulting MCS. Design/methodology/approach: We shared the view that organizational reality is negotiated and constructed by collective participants' consciousness. The study used interpretive case study. Interviews, observation and documentary analysis were used to collect the data. Findings: Leadership and MCS of family business is embedded in its societal culture. A leader–owner is not a creator but a mere manager of organizational culture because he/she is also a product of the societal culture. The owner and his/her inner circle (family and non-family members) may collectively play crucial roles in producing and reproducing the legitimate MCS based on the extended family concept. In this sense, cultural control based on shared family norms is the most dominant one and simplifies process and result controls. However, business pragmatism may go hand-in-hand with the culture in giving room for MCS transformations. Research limitations/implications: The family business under study is still run by the family's first generation, has no subsidiaries and is embedded in Javanese paternalistic culture. Although rich in details, the sample size of the study is a limitation. Practical implications: This study encourages the owners of a family business to consider the use of strong cultural control along with bureaucratic controls to create a sustainable organisation. Originality/value: This study offers insight to help understand and explain how leadership and MCS practices in family business are embedded in broader societal culture in less developed countries.